Possible role of PKC in regulation of neuronal serotonin uptake and 5-HT(2A) receptor. - Rahimian, Roshanak. (University of Ottawa (Canada), 1995)
We investigated whether neuronal serotonin uptake is regulated by PKC. ($\sp3$H) 5-HT uptake and its kinetics parameters (Km and Vmax) were measured in the synaptosomal (P$\sb2$) fraction of brain tissue in vitro in the presence of different concentration of 4$\beta$-phorbol-12 myristate-13-acetate (PMA) and of a selective 5-HT uptake inhibitor, citalopram. Exposure of cortical synaptosomes to citalopram produced a marked decrease of 5-HT uptake at all time intervals of pre-incubation. However, the PKC activator PMA failed to produce unequivocal changes in the tate of 5-HT uptake by cortical synaptosomes of the rat brain. This study was undertaken to explore further 5-HT$\sb{\rm 2A}$ receptor regulation by agonist treatment in vivo and the role of PKC in this regulation. Single injection of 1-(2,5-dimethoxy-4-iodo-phenyl)2-amino-propane (DOI) down-regulated 5-HT$\sb{\rm 2A}$ receptor density in cortical synaptosomal preparation assayed 24 hours later by ($\sp3H$) ketanserin binding as well as in homogenate of rat cerebral cortex. Single high doses but not a low dose of DOI reduced the Bmax of 5-HT$\sb{\rm 2A}$ receptors in cortical synaptosomes labelled with ($\sp3$H) ketanserin without significant changes in Kd. Repeated doses of DOI further down-regulated 5-HT$\sb{\rm 2A}$ sites in cortical synaptosomes, without altering the Kd value. PKC activity in both particulate and soluble fraction of rat cortical synaptosomes was measured by incorporation of ($\sp{32}$P) ATP into a specific target PKC The increase of PKC activity in the particulate fraction of the cortical synaptosomal tissue following single injection of DOI parallelled the decrease in 5-HT$\sb{\rm 2A}$ receptor density assessed with ($\sp3$H!) etanserin, suggesting that 5-HT$\sb{\rm 2A}$ sites may be down-regulated as a result of phosphorylation of the receptor by activation of PKC after receptor stimulation with agonist. (Abstract shortened by UMI.)
Keywords: Biology, Neuroscience.